2016
DOI: 10.4172/2157-7579.1000397
|View full text |Cite
|
Sign up to set email alerts
|

Contact-Independent Antagonism of Ophidiomyces ophiodiicola, the Causative Agent of Snake Fungal Disease by Rhodococcus rhodochrous DAP 96253 and Select Volatile Organic Compounds

Abstract: Snake fungal disease (SFD), caused by the ascomycete Ophidiomyces ophiodiicola, has been associated with severe morbidity and mortality of numerous species of wild snakes in 15 US states. Accordingly, SFD was added to the horizon scan of global conservation issues in 2014. Due to the itinerant and secluded nature of many snake species, as well as the diversity of species impacted by SFD, estimating SFD-associated mortalities has been challenging. Regardless, the impacts have been shown to be significant in loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…), and Ophidiomyces ophiodiicola , the causative agent of snake fungal disease (SFD) of reptiles (Cornelison et al . ). Additionally, several antifungal susceptibility assays with synthetic formulations were conducted with previously discovered antifungal VOCs (Fernando et al .…”
Section: Biomimicrymentioning
confidence: 97%
See 4 more Smart Citations
“…), and Ophidiomyces ophiodiicola , the causative agent of snake fungal disease (SFD) of reptiles (Cornelison et al . ). Additionally, several antifungal susceptibility assays with synthetic formulations were conducted with previously discovered antifungal VOCs (Fernando et al .…”
Section: Biomimicrymentioning
confidence: 97%
“…Several microbially produced, antifungal VOCs have been identified from the scientific literature for their potential to be used for microbial control and disease management. Previous studies have demonstrated the ability of these microbially produced VOCs, as well as formulations comprised of several VOCs, to inhibit fungal mycelia growth, conidia viability, pigment production and virulence, when tested in the gaseous phase (Bruce et al 2003;Fernando et al 2005;Li et al 2010;Yuan et al 2012;Wang et al 2013;Cornelison et al 2014aCornelison et al , 2016Wu et al 2015;Toffano et al 2017). However, these studies have not attempted deep probing of soil communities and, therefore, suggest a tremendous untapped potential for the discovery of antimicrobials from fungistatic soil communities.…”
Section: Vocs As Antimicrobialsmentioning
confidence: 99%
See 3 more Smart Citations